2023
DOI: 10.1128/msphere.00522-22
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Antibody Prevalence among Industrial Livestock Operation Workers and Nearby Community Residents, North Carolina, 2021 to 2022

Abstract: Few studies have measured COVID-19 seroprevalence in North Carolina, especially among rural, Black, and Hispanic/Latino communities that have been heavily affected. Antibody results show high rates of COVID-19 among industrial livestock operation workers and their household members.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…[24]observationalUSAmask mandates for reducing transmissionnucleic acid or antigenmandate dataGigot et al . [25]observationalUSAmasks for reducing transmissionsaliva antibody testingquestionnaireGoncalves et al . [26]observationalBrazilmasks for reducing transmissionRT-PCR or antibody testing (non-specific)interviewHast et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24]observationalUSAmask mandates for reducing transmissionnucleic acid or antigenmandate dataGigot et al . [25]observationalUSAmasks for reducing transmissionsaliva antibody testingquestionnaireGoncalves et al . [26]observationalBrazilmasks for reducing transmissionRT-PCR or antibody testing (non-specific)interviewHast et al .…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies reported on the effectiveness of masks for reducing transmission of SARS-CoV-2 as their primary outcome: 24 studies (two RCTs, 22 observational) in community settings [1418,20,21,23,2527,29,33,34,3641,43,44,46,48] and 23 observational studies in healthcare settings [50,5361,6366,68,69,7577,81,82,84,85].…”
Section: Resultsmentioning
confidence: 99%
“…48 The association between race, immune response, and disease severity highlights the importance of assessing demographic features for protection against SARS-CoV-2. 43,49 Further, demographic-based risk assessment and monitoring of HCWs to enhance their protection and ensure a safe work environment is critical. Additionally, maintenance of the vaccine schedule and adherence to booster doses have been shown…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported on demographics and antibody results for all participants of any age and industry (including not employed) enrolled between February 2021 and July 2022 (Gigot et al 2023). Study enrollment continued for one additional month.…”
Section: Study Design and Populationmentioning
confidence: 99%